Ageing of 100Cr6 steel: synchrotron X-ray diffraction and dimensional analysis investigation. Issue 11 (23rd July 2016) - Lejay, V.; Sidoroff, C.; Le Bourlot, C.; Perez, M.; Dierickx, P.
Abstract : Thermal ageing of 100Cr6 with different initial austenitisings was studied using the combination of synchrotron X-ray diffraction and dimensional variation measurements. Synchrotron X-ray diffraction provided the phase volume fractions and their carbon content through the analysis of the lattice parameters. Dimensional measurements were obtained in situ in a quench dilatometer also used to realise the heat treatment. The combined analysis of these data provides a better understanding of phase evolutions. For the different austenitising treatments investigated, the dimensional variations were found to be easily linked to the phase parameters measured by X-ray diffraction. This paper is part of a Themed Issue on Recent developments in bearing steels.